2019
DOI: 10.3390/biom9060233
|View full text |Cite
|
Sign up to set email alerts
|

IL7RA rs6897932 Polymorphism Is Associated with Better CD4+ T-Cell Recovery in HIV Infected Patients Starting Combination Antiretroviral Therapy

Abstract: Interleukin-7 receptor subunit alpha (IL7RA) rs6897932 polymorphism is related to CD4+ recovery after combination antiretroviral therapy (cART), but no studies so far have analyzed its potential impact in patients with very low CD4+ T-cells count. We aimed to analyze the association between IL7RA rs6897932 polymorphism and CD4+ T-cells count restoration in HIV-infected patients starting combination antiretroviral therapy (cART) with CD4+ T-cells count <200 cells/mm3. We performed a retrospective study in 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…The CCL3L1‐CCR5 genotypes, polymorphisms in CD14 and TLR4, mitochondrial haplogroup H, and IL18 G variant allele and genotype were associated with enhanced long‐term CD4 + T‐cell recovery in HIV‐1‐infected patients on suppressive ART. The IL‐7 receptor subunit alpha (IL7RA) rs6897932 CT/TT genotype was related to a faster and better CD4 + T‐cells recovery compared to that of the CC genotype; a potential mechanism is that signal transduction and proliferation in response to IL‐7 was is substantially higher in the "TT" genotype compared to that in the "CC" genotype in HIV‐infected individuals . A study by Greenblatt et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCL3L1‐CCR5 genotypes, polymorphisms in CD14 and TLR4, mitochondrial haplogroup H, and IL18 G variant allele and genotype were associated with enhanced long‐term CD4 + T‐cell recovery in HIV‐1‐infected patients on suppressive ART. The IL‐7 receptor subunit alpha (IL7RA) rs6897932 CT/TT genotype was related to a faster and better CD4 + T‐cells recovery compared to that of the CC genotype; a potential mechanism is that signal transduction and proliferation in response to IL‐7 was is substantially higher in the "TT" genotype compared to that in the "CC" genotype in HIV‐infected individuals . A study by Greenblatt et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…a potential mechanism is that signal transduction and proliferation in response to IL-7 was is substantially higher in the "TT" genotype compared to that in the "CC" genotype in HIV-infected individuals. [187][188][189] A study by Greenblatt et al showed that 41 genes harbored variations that were independently predictive of CD4 recovery. Many of these genes are associated with the cell cycle, apoptosis, lymphocyte migration, or CD4 + T-cell homeostasis.…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…They include low baseline antibody responses to Cryptococcus spp., e.g., decreased levels of total plasma IgM and specific antifungal IgM (GXM-IgM or β-glucanbinding IgM) [28], and a lack of pro-inflammatory cytokines in the serum, or CSF, as described below. Genetic factors, such as single nucleotide polymorphism Interleukin 7 receptor subunit alpha (IL7RA), may affect predisposition in the development of IRIS [29]. Allelic polymorphisms (e.g., in CYP2C19 gene) may be considered as patient-specific risk factors affecting fungicidal drug activities, toxicity, and the level of inflammation (e.g., C-reactive protein or albumin levels) [30].…”
Section: Host-related Risk Factorsmentioning
confidence: 99%
“…[81,88]. Recent genetic studies revealed that the T allele homozygosity at rs6897932 of the L-7R gene (encodes CD127) links to a faster CD4+ T cell recovery after ART initiation, as opposed to CC genotypes in HIV-infected individuals [29,89].…”
Section: Blood Plasma and Serum Biomarkers In Cm-irismentioning
confidence: 99%
“…Unmasking CM-IRIS may include neurological symptoms driven by high intracranial pressure and pathways proposed as potential baseline biomarkers, as described below [28]. Genetic factors, such as single nucleotide polymorphism Interleukin 7 receptor subunit alpha (IL7RA) may affect predisposition to developing of IRIS [29]. Allelic polymorphisms (e.g.…”
Section: Introductionmentioning
confidence: 99%